194k views
4 votes
How can one third x − 2 = one fourth x + 11 be set up as a system of equations?

User Fiffe
by
5.6k points

2 Answers

4 votes

Answer: (x-2) = (x+11)

------- -------

3 4

Explanation:

First part is x-2 divided by on third. So the x-2 acts a the 1 so you put x-2 over 3. And you get:

(x-2)

--------

3

For the other side of the equation it is x +11 divide by 1/4. So the x+11 will act a the 1 in the fraction. And you will get:

(x+11)

--------

4

User Tutu
by
5.4k points
4 votes

For this case we have the following expression:


\frac {1} {3} (x-2) = \frac {1} {4} (x + 11)

So, we have two equations of the form:
y = \frac {1} {3} (x-2)\\y = \frac {1} {4} (x + 11)

Rewriting equation 1:


y = \frac {1} {3} (x-2)\\3y = x-2\\3y-x = -2

If we multiply by 3 on both sides of the equation we have:


9y-3x = -6

Rewriting equation 2:


y = \frac {1} {4} (x + 11)\\4y = x + 11\\4y-x = 11

If we multiply by 4 on both sides of the equation:


16y-4x = 44

Answer:


9y-3x = -6\\16y-4x = 44

User Bitlamas
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.